EFFECT OF SEX AND AGE ON MORPHOMETRIC, PHYSIOLOGICAL AND BLOOD PROFILE OF MIXED BRED RABBIT - Ihendu, U.; Atansuyi, A. J.; Chineke, C.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
This study was conducted to assess the morphometric, physiological and blood parameters of mixbred rabbits at different ages. One hundred and sixty rabbits comprising New Zealand White and Chinchilla Crossbreds were used. Body weight and body linear parameters were measured and recorded on weekly basis. Generalised Linear Model Procedure of SAS software was used to analyse the data set to examine the effects of sex and age on these parameters. The results indicated that sex significantly (P<0.05) affected morphometric and physiological parameters at 4, 8, 12, 32 and 48 weeks. Does (female rabbits) performed better than bucks (male rabbits) in almost all the traits studied. Buck at 8 weeks had higher rectal temperature while, higher values for pulse rate were recorded among the does and bucks at 32 weeks. Higher respiratory rate was observed in bucks at 48 weeks and for does at 32-48 weeks. Sex however had no significant effect on all haematological parameters. Sex had significant effect (P<0.05) on aspartate amino transferase (AST), alanine amino transferase (ALT), alkaline phosphate (ALP), cholesterol (CHOL), triglyceride (TRG), low density lipoprotein (LDL), urea, creatinine and globulin (GLOB) of the crossbred rabbits at different ages. The higher aspartate amino transfererase (AST), alanine amino transferase (ALT), alkaline phosphate (ALP), cholesterol (CHOL), triglyceride (TRG), low density lipoprotein (LDL), globulin (GLOB) and urea were recorded in bucks at 48 weeks while the lowest low-density lipoprotein (LDL) was recorded for bucks at 32 weeks but creatinine was higher at 48 weeks of age among the does. Age had significant (P<0.05) effect on morphometric, physiological and blood parameters. The highest rectal temperature was recorded at 8 weeks of age while highest respiratory rate was recorded for rabbits at 48 weeks. The higher creatinine, basophils and urea values were recorded for rabbits at 48 weeks old. Body weight influenced the morphometric, physiology and blood parameter of crossbred rabbits. It can be suggested to rabbit farmers that sex and age must be taken into account for optimal production.